Analisis Dampak Current Ratio dan Debt to Assets Ratio terhadap Return on Asset pada Perusahaan Farmasi - Karmiyati, Sari (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
The purpose of this research is to determine the influence of the Current Ratio (CR) and Debt to Equity Ratio on Return on Assets (ROA) partially and simultaneously in 10 pharmaceutical companies registered on the IDX that meet the criteria, namely the company is not delisted and always publishes reports finances that can be accessed during the observation period. Researchers used quantitative descriptive methods, the financial reports studied were in the 2020-2023 period, while multiple linear regression was used to prove the influence between variables. The research method used is associative with a quantitative approach. The panel data regression method chosen is the Common Effect Model. The research results show that CR has a significant positive effect on ROA, but DAR has no effect on ROA. CR and DAR influence ROA simultaneously and significantly.